Predisposing causes for pregnancy among adolescents - Emanuela Batista Ferreira; Juliana Lourenço Araújo Veras; Sâmara Aline Brito; Edlainy Andrade Gomes; Janaína Pontes de Albuquerque Mendes; Jael Maria de Aquino (Universidade Federal do Estado do Rio de Janeiro, 2014)
Objective: This study aimed to describe the predisposing causes for pregnancy among adolescents and theirknowledge on the prevention methods. Method: This is an exploratory, descriptive, and quantitative research carried out at basic health units in the town of Sao Caetano, Pernambuco, Brazil, in September and October 2011. For data collection, one used a semi-structured questionnaire applied to 42 adolescents enrolled for prenatal care. Results: The findings show that most adolescents was around 16 years of age, brown skinned, literate, and Catholic, lived with her partner, and had a low socioeconomic status. One's own wish (54.8%) stood out as the main cause for pregnancy in the population under study. Conclusion: One found out there's a need for investing on strategies for providing these female adolescents with guidance, so that contraceptive practices and the responsible exercise of sexuality start being realized as positive and usual behaviors.